Akulah Terang Dunia: Eksegesis Yohanes 8:12 dan Relevansinya dalam Iman Kristen - Pamarto, Ageng Asih (Views : Jurnal Teologi dan Biblika, 2025)
This article explores the theological and spiritual meaning of Jesus’ statement, I am the light of the world (John 8:12), through a historical-grammatical exegesis approach. The study highlights the historical context of Jesus' declaration, namely the Feast of Tabernacles (Sukkot), where He presented Himself as the fulfillment of light symbolism in Jewish tradition and Messianic prophecies. An in-depth analysis of the Greek text reveals the linguistic power of the ἐγώ εἰμι (ego eimi) claim affirming His divinity, as well as the οὐ μὴ (ou mē) promise guaranteeing absolute freedom from darkness and the gift of the light of life. The findings demonstrate that John 8:12 shifts the focus of Christian faith from legalism to a personal relationship with Christ as the living God. The article also discusses its theological and spiritual relevance, affirming Jesus as the source of guidance, certainty, and meaning in facing life’s darkness.